Feasibility of telemedicine for patients with parkinsonism in the Brazilian public health system - Santos, Daniel Teixeira; Camelo, Daniel Monte Freire; Strelow, Matheus Zschornack; Silva, Maysa Tayane Santos; Führ, Paula; Marins, Letícia Winer; Schumacher-Schuh, Artur Francisco (Arquivos de Neuro-Psiquiatria, 2022)
Background Telemedicine for patients with parkinsonism is feasible, cost-effective and satisfactory. However, the feasibility of this modality of care for this subpopulation is not known in real-life scenarios of developing countries like Brazil.Objective To evaluate the feasibility of telemedicine for patients with parkinsonism in a developing country.Methods A cross-sectional study with patients with parkinsonism treated in the Brazilian public healthcare system. We included 130 patients, who were contacted by telephone; those who could be reached underwent a structured interview for data collection. The primary outcomes were the feasibility of teleconsultations and video consultations, but we also performed a logistic regression regarding the feasibility of a video consultation and associated factors.Results Telemedicine was feasible and accepted by 69 (53.08%) patients regarding teleconsultations and by 50 (38.5%) patients regarding video consultations. Teleconsultations were feasible for 80.2%, and video consultations were feasible for 58.1% of the patients reachable through telephone calls. Having a higher family income was positively correlated with the feasibility for a video consultation while a negative association was observed regarding being married or in a stable union and having a low level of schooling.Conclusions A significant proportion of patients with parkinsonism in a developing country are unreachable, unwilling, or unable to participate in telemedicine. Among the reachable patients, feasibility is higher but still lower than what is reported in studies in developed countries. Family income, level of schooling, and marital status were associated with the feasibility of video consultations.
Keywords: Parkinsonian Disorders; Parkinson Disease; Telemedicine; Remote Consultation